Evaluasi Ergonomi pada Kursi Roda untuk Anak Cerebral Palsy Menggunakan Digital Human Modeling - Dwi Rahmalina; Desinta Rahayu Ningtyas; Nur Yulianti Hidayah; Agri Suwandi; Dede Lia Zariatin; I Gede Eka Lesmana Lesmana; Dhidik Mahandika; Susanto Sudiro (Fakultas Teknik Universitas Pancasila, 2023)
Cerebral palsy is caused by brain damage that manifests as motor dysfunction. The most prevalent form of cerebral palsy is spastic diplegia, which causes walking difficulties. People with cerebral palsy, particularly children, require mobility aids, such as wheelchairs, to perform daily tasks. When designing wheelchairs for children with cerebral palsy, ergonomic evaluation is required to ensure that the resulting wheelchair is safe and will not pose a risk in the future. This paper investigates the use of digital human modeling to evaluate the ergonomics of wheelchairs for children with cerebral palsy. The method is used to collect samples from 5 to 18-year-old children with cerebral palsy. Digital human modeling is used to simulate and evaluate ergonomics using anthropometric data. The results obtained for the wheelchair dimensions are suitable for the 95th percentile value, while the seat length exceeds the popliteal length for the 50th percentile value. The ergonomic evaluation yielded satisfactory results for the lower back analysis parameter, and the comfort evaluation yielded satisfactory results for the 95th percentile value. In contrast, the 5th percentile value indicates knee discomfort in both the right and left knee.